miR-137 and miR-491 Negatively Regulate Dopamine Transporter Expression and Function in Neural Cells - Xiaojian Jia; Feng Wang; Ying Han; Xuewen Geng; Minghua Li; Yu Shi; Lin Lu; Yun Chen (Neuroscience Bulletin, 2016)

Induced Pluripotent Stem Cells in Huntington’s Disease: Disease Modeling and the Potential for Cell-Based Therapy - Ling Liu; Jin-Sha Huang; Chao Han; Guo-Xin Zhang; Xiao-Yun Xu; Yan Shen; Jie Li; Hai-Yang Jiang; Zhi-Cheng Lin; Nian Xiong; Tao Wang (Molecular Neurobiology, 2016)

N-cadherin regulates beta-catenin signal and its misexpression perturbs commissural axon projection in the developing chicken spinal cord - Ciqing Yang; Xiaoying Li; Congrui Wang; Sulei Fu; Han Li; Zhikun Guo; Shanting Zhao; Juntang Lin (Journal of Molecular Histology, 2016)

Alterations to biological soil crusts with alpine meadow retrogressive succession affect seeds germination of three plant species - Yi-kang Li; Jing-zheng Ouyang; Li Lin; Xing-liang Xu; Fa-wei Zhang; Yan-gong Du; Shu-li Liu; Guang-min Cao; Fa Han (Journal of Mountain Science, 2016)

RhoB/ROCK mediates oxygen–glucose deprivation-stimulated syncytiotrophoblast microparticle shedding in preeclampsia - Jian Han; Bo-ping Yang; Yi-lin Li; Hong-mei Li; Xiu-hui Zheng; Li-li Yu; Qiong Zhang; Ying-ru Zheng; Ping Yi; Li Li; Jian-xin Guo; Yuan-guo Zhou (Cell and Tissue Research, 2016)

Induced growth promotion and higher salt tolerance in the halophyte grass Puccinellia tenuiflora by beneficial rhizobacteria - Shu-Qi Niu; Hui-Ru Li; Paul W. Paré; Mina Aziz; Suo-Min Wang; Huazhong Shi; Jing Li; Qing-Qing Han; Shi-Qian Guo; Jian Li; Qiang Guo; Qing Ma; et al. (Plant and Soil, 2016)

Wnt5a mediated canonical Wnt signaling pathway activation in orthodontic tooth movement: possible role in the tension force-induced bone formation - Hai-Di Fu; Bei-Ke Wang; Zi-Qiu Wan; Heng Lin; Mao-Lin Chang; Guang-Li Han (Journal of Molecular Histology, 2016)

Assessment of the seasonal variation of simulated Wyrtki jet over the tropical Indian Ocean in CMIP5 models - Lin Liu; Baochao Liu; Guoqing Han; Lin Feng; Xinfang Li; Weidong Yu (Arabian Journal of Geosciences, 2016)

Synergistic antitumor activity of triple-regulated oncolytic adenovirus with VSTM1 and daunorubicin in leukemic cells - Jiao Zhou; Qiu-Mei Yao; Jin-Lan Li; Yan Chang; Ting Li; Wen-Ling Han; Hong-Ping Wu; Lin-Fang Li; Qi-Jun Qian; Guo-Rui Ruan (Apoptosis, 2016)

Microbacterium gilvum sp. nov., isolated from civet faeces - Xiu Chen; Qin-Yuan Li; Gui-Ding Li; Fang-Ji Xu; Yi Jiang; Li Han; Cheng-Lin Jiang; Xue-Shi Huang (Antonie van Leeuwenhoek, 2016)

Hypocrol A, a new tyrosol derivative from a sponge-derived strain of the fungus Hypocrea koningii - Li-Jian Ding; Wei Yuan; Ying-Xin Li; Xiao-Jian Liao; Huan Sun; Qi Peng; Bing-Nan Han; Hou-Wen Lin; Zhi-Yong Li; Fan Yang; Shi-Hai Xu (Natural Product Research, 2016)

From folding to transpressional faulting: the Cenozoic Fusha structural belt in front of the Western Kunlun Orogen, northwestern Tibetan Plateau - Cong Wang; Xiao-Gan Cheng; Han-Lin Chen; Kang Li; Xiao-Gen Fan; Chun-Yang Wang (International Journal of Earth Sciences, 2016)

Gene characterization and transcription analysis of two new ammonium transporters in pear rootstock (Pyrus betulaefolia) - Hui Li; Jin-Long Han; You-Hong Chang; Jing Lin; Qing-Song Yang (Journal of Plant Research, 2016)

Human amniotic epithelial stem cells promote wound healing by facilitating migration and proliferation of keratinocytes via ERK, JNK and AKT signaling pathways - Bin Zhao; Jia-Qi Liu; Zhao Zheng; Jun Zhang; Shu-Yue Wang; Shi-Chao Han; Qin Zhou; Hao Guan; Chao Li; Lin-Lin Su; Da-Hai Hu (Cell and Tissue Research, 2016)

Temperature dependent defence of Nicotiana tabacum against Cucumber mosaic virus and recovery occurs with the formation of dark green islands - Feifei Zhao; Yanan Li; Lijuan Chen; Lisha Zhu; Han Ren; Honghui Lin; Dehui Xi (Journal of Plant Biology, 2016)

Site-related and seasonal variation of bioaerosol emission in an indoor wastewater treatment station: level, characteristics of particle size, and microbial structure - Wenjie Ding; Lin Li; Yunping Han; Jianzhong Liu; Junxin Liu (Aerobiologia, 2016)

New naphthopyrones from marine-derived fungus Aspergillus niger 2HL-M-8 and their in vitro antiproliferative activity - Da-Hong Li; Tong Han; Li-Ping Guan; Jiao Bai; Nan Zhao; Zhan-Lin Li; Xin Wu; Hui-Ming Hua (Natural Product Research, 2016)

Blood Cadmium Level Associates with Lower Testosterone and Sex Hormone-Binding Globulin in Chinese men: from SPECT-China Study, 2014 - Chi Chen; Ningjian Wang; Xiaomin Nie; Bing Han; Qin Li; Yi Chen; Hualing Zhai; Chunfang Zhu; Yingchao Chen; Fangzhen Xia; Meng Lu; Dongping Lin; et al. (Biological Trace Element Research, 2016)

Upregulation of Dickkopf1 by oscillatory shear stress accelerates atherogenesis - Mengmeng Li; Xinxin Liu; Yu Zhang; Mingxue Di; Han Wang; Lin Wang; Yifei Chen; Xiaoling Liu; Xiaoqing Cao; Renya Zeng; Yun Zhang; Mei Zhang (Journal of Molecular Medicine, 2016)

Correlation between the germline methylation status in ERβ promoter and the risk in prostate cancer: a prospective study - Lihui Wang; Pan Zhang; Xiannan Meng; Xiang Chen; Zou Xiang; Xiaoqian Lin; Ye Liu; Weidong Gan; Xiaodong Han; Dongmei Li (Familial Cancer, 2016)

PI3K/Akt/FoxO3a signaling mediates cardioprotection of FGF-2 against hydrogen peroxide-induced apoptosis in H9c2 cells - Mi-Hua Liu; Guo-Hua Li; Li-Jun Peng; Shun-Lin Qu; Yuan Zhang; Juan Peng; Xin-Yuan Luo; Heng-Jing Hu; Zhong Ren; Yao Liu; Hui Tang; Lu-Shan Liu; et al. (Molecular and Cellular Biochemistry, 2016)

QTL mapping of flag leaf traits in common wheat using an integrated high-density SSR and SNP genetic linkage map - Qiuhong Wu; Yongxing Chen; Lin Fu; Shenghui Zhou; Jiaojiao Chen; Xiaojie Zhao; Dong Zhang; Shuhong Ouyang; Zhenzhong Wang; Dan Li; Guoxin Wang; Deyun Zhang; et al. (Euphytica, 2016)

Humic acids enhance the microbially mediated release of sedimentary ferrous iron - Chun-Han Chang; Chia-Cheng Wei; Li-Hung Lin; Tzu-Hsuan Tu; Vivian Hsiu-Chuan Liao (Environmental Science and Pollution Research, 2016)

Characterization of the novel T4-like Salmonella enterica bacteriophage STP4-a and its endolysin - Meng Li; Mengzhe Li; Hong Lin; Jingxue Wang; Yanqiu Jin; Feng Han (Archives of Virology, 2016)

New magnetostratigraphic and pedostratigraphic investigations of loess deposits in north‐east China and their implications for regional environmental change during the Mid‐Pleistocene climatic transition - Lin Zeng; Huayu Lu; Shuangwen Yi; Yongxiang Li; Anqi Lv; Wenchao Zhang; Zhiwei Xu; Haifeng Wu; Han Feng; Mengchun Cui (Journal of Quaternary Science, 2016)
Little is known about the long‐term climatic evolution of north‐eastern (NE) China, because well‐preserved terrestrial paleoenvironmental archives are scarce in this vast region. The extensive loess deposits in the Chifeng region are the thickest and most complete loess–paleosol sequence in NE China, and have significant potential for reconstructing the paleoclimate of the region. Here, we present new high‐resolution magnetostratigraphic results from two loess–paleosol sections in the Chifeng region: the Sanbahuo (SBH) and Toudaojingzi (TDJZ) sections. The results demonstrate that both sections record the Brunhes normal polarity chron and the upper portion of the Matuyama reversed polarity chron. Based on these new results, the base of the TDJZ loess sequence is dated at ca. 1.22 Ma, representing the oldest known loess deposits in NE China. The initiation of loess accumulation in NE China was roughly synchronous with the large expansion of the Eurasian loess belt during the late Early Pleistocene (1.2–0.7 Ma), probably reflecting a widespread intensification of aridity in northern mid‐latitudes. We suggest that global cooling during the Mid‐Pleistocene climatic transition led to increased aridity and more favorable conditions for promoting the availability of silt for entrainment, transport and deposition.